2003
DOI: 10.1029/2002jd002425
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of positively and negatively charged particles inside PMSE during MIDAS SOLSTICE 2001

Abstract: A magnetically shielded, charge collecting rocket probe was used on two flights in the MIddle Atmosphere Dynamics and Structure (MIDAS) Studies of Layered STructures and ICE (SOLSTICE) 2001 rocket campaign over Andøya, Norway. The probe was a graphite collection surface with a permanent magnet underneath to deflect electrons. The first MIDAS was launched 17 June 2001 into a strong, multiply layered PMSE. The probe measured negative particles inside an electron biteout within the PMSE, having a peak charge numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…Havnes et al (1996) flew a Faraday cup through NLC and found negative particles but also positive particles in number densities too large to be accounted for by the standard plasma charging model. Positive particles have also been observed by detectors of different designs Smiley et al, 2003) and in the absence of NLC conditions (Gelinas et al, 1998;Rapp et al, 2005;Amyx et al, 2008). The possibility of photoelectric charging has been considered (Havnes et al, 1990;Rapp and Lübken, 1999), but this would require a reduction of the work function of ice by easily-ionized impurities such as sodium.…”
Section: Introductionmentioning
confidence: 93%
“…Havnes et al (1996) flew a Faraday cup through NLC and found negative particles but also positive particles in number densities too large to be accounted for by the standard plasma charging model. Positive particles have also been observed by detectors of different designs Smiley et al, 2003) and in the absence of NLC conditions (Gelinas et al, 1998;Rapp et al, 2005;Amyx et al, 2008). The possibility of photoelectric charging has been considered (Havnes et al, 1990;Rapp and Lübken, 1999), but this would require a reduction of the work function of ice by easily-ionized impurities such as sodium.…”
Section: Introductionmentioning
confidence: 93%
“…In subsequent campaigns, several investigations have provided further evidence for the existence of negatively charged aerosol particles in PMSE (e.g. Havnes et al 2001;Smiley et al 2003;Rapp et al 2009). Concerning positively charged particles there seem to be further indications that they do exist (Mitchell et al , 2003Smiley et al 2003), however, our current understanding of these measurements is far from being conclusive: While it was shown in the laboratory by Vondrak et al (2006) that ice particles with a surface contamination with as little as 0.02 monolayers of sodium atoms could potentially charge positively by photoemission in the rare event of the fresh metal input from a rather large meteoroid, Havnes and Naesheim (2007) have recently argued that the positive charge observed during the original flight in 1994 was likely created by secondary charging effects inside their instrument.…”
Section: Charged Particle Measurements In Pmse-environmentsmentioning
confidence: 98%
“…We know today that visual and subvisual dust can exist at polar latitudes during the summer when the temperature near the mesopause is low (Havnes et al, 1996;Croskey et al, 2001;Smiley et al, 2003). For the small dust below several nanometers in diameter we have only theoretical, unconfirmed estimates of 'smoke' particles formed by evaporated material from meteorites.…”
Section: Introductionmentioning
confidence: 96%